Korelasi Moderasi Agama dengan Ajaran Manunggaling Kawula Gusti Syekh Siti Jenar - Ulviana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
In social life, humans do not escape from their social groups, whether it is from the point of view of culture, religion, or certain sects with the same ideology. From this diversity, they need policies that are suitable for all groups, such as the policy of the Indonesian Ministry of Religion which implements the mission of religious moderation. Departing from the question, what kind of religious moderation is meant by the Indonesian Ministry of Religion?. This makes the concept of religious moderation which is correlated with the concept of manunggaling kawulo Gusti Syekh Siti Jenar very important in human life. Because it shows that the value of Sufism in the concept of manunggaling kawulo Gusti Syekh Siti Jenar will exist with the world of religious moderation or not. This research is a qualitative research in which the data collection is done by means of documentation, then the data is analyzed by means of content analysis. The data is obtained from literature relevant to the teachings of Manunggaling Kawula Gusti Syekh Siti Jenar. This study concludes that the religious moderation launched by the Ministry of Religion of the Republic of Indonesia is actually not much different from the concept of Manunggaling Kawula Gusti from Sheikh Siti Jenar seen from the implementation of both, especially on the principle of fairness and balance.